2022
DOI: 10.3389/fchem.2022.1024177
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in photothermal therapy-based multifunctional nanoplatforms for breast cancer

Abstract: Breast cancer (BC) is one of the most common cancers in women worldwide; however, the successful treatment of BC, especially triple-negative breast cancer (TNBC), remains a significant clinical challenge. Recently, photothermal therapy (PTT), which involves the generation of heat under irradiation to achieve photothermal ablation of BC with minimal invasiveness and outstanding spatial–temporal selectivity, has been demonstrated as a novel therapy that can overcome the drawbacks of chemotherapy or surgery. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…So, choosing proper therapeutic agents is challenging for other patients (due to tumor heterogenicity), and the stem cells are resistant by nature. So, nanoparticle‐mediated thermal therapy is used to kill those refractory BCSCs selectively (Sun et al, 2022). Amongst all the nanoplatforms mentioned before, carbon nanotubes (Neves et al, 2013; Singh & Torti, 2013), gold‐based nanoparticles (Liu, Crawford, & Vo‐Dinh, 2018), and iron oxide nanoparticles (Paholak et al, 2016) have been the predominant platforms for the thermal therapy of BCSCs.…”
Section: Nanomedicine‐based Breast Cancer Stem Cell Eradicationmentioning
confidence: 99%
“…So, choosing proper therapeutic agents is challenging for other patients (due to tumor heterogenicity), and the stem cells are resistant by nature. So, nanoparticle‐mediated thermal therapy is used to kill those refractory BCSCs selectively (Sun et al, 2022). Amongst all the nanoplatforms mentioned before, carbon nanotubes (Neves et al, 2013; Singh & Torti, 2013), gold‐based nanoparticles (Liu, Crawford, & Vo‐Dinh, 2018), and iron oxide nanoparticles (Paholak et al, 2016) have been the predominant platforms for the thermal therapy of BCSCs.…”
Section: Nanomedicine‐based Breast Cancer Stem Cell Eradicationmentioning
confidence: 99%
“…Recent studies have demonstrated the benefits of combining PTT with other therapeutic modalities, including photodynamic treatment (PDT), chemotherapy (CT), radiotherapy and immunotherapy [80]. Multimodal therapies provide opportunities to exploit the advantages and avoid the drawbacks of each single modality, leading to additive and synergistic therapeutic effects [80,82]. For instance, the simultaneous use of PTT with PDT can help to decrease the laser intensity and shorten its irradiation time compared to using PTT or PDT alone.…”
Section: Cancer Therapy By Pttmentioning
confidence: 99%
“…However, it is still difficult to combine hyperthermia with other therapies in a consistent, efficient and structured way, which is a clinical challenge that needs to be overcome ( Meng et al, 2022a ). Photothermal therapy (PTT) is capable of non-invasive thermal ablation of cancers mediated by photothermal converters and has been shown to be an emerging therapy for selective killing of cancer cells with the advantages of high efficiency, high stability, high temporal and spatial selectivity, and low invasive load ( Kadkhoda et al, 2022 ; Sun et al, 2022 ). Photodynamic therapy (PDT) is able to kill cancer cells oxidatively and induce their immunogenic death with the help of photosensitizers that produce reactive oxygen species ( Zhou et al, 2022a ; Zhou et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%